Novel immune assay for quantification of plasma protective capacity against oxidized phospholipids. (August 2016) - Bochkov, Valery; Schoenenberger, Andreas W; Oskolkova, Olga; Toth, Ursula; Stöckl, Johannes; Majdic, Otto; Daci, Armond; Resink, Thérèse J; Erne, Paul; Philippova, Maria
Aim: Oxidized phospholipids (OxPL) are the major pathogenic component of oxidized low-density lipoproteins (OxLDL). Endogenous anti-OxPL activity, defined as the ability to neutralize adverse effects of oxidized lipids, may have biomarker potential.Methods & results: Using two anti-OxPL monoclonal antibodies (commercial mAB-E06 and custom mAB-509) we developed a novel ELISA that measures the global capacity of plasma to inactivate OxPL. Preincubation of OxLDL with plasma inhibits its binding of anti-OxPL mABs. This phenomenon ('masking') reflects anti-OxPL plasma activity. A pilot clinical application of the assay revealed reduced anti-OxPL activity in hypertension, coronary artery disease, acute coronary syndrome and diabetes.Conclusion: Inadequate anti-OxPL protection may contribute to cardiovascular disease and have biomarker potential in conditions associated with abnormal lipid peroxidation.